PERKEMBANGAN PERMUKIMAN PINGGIRAN KOTA DI KELURAHAN PESANTREN KECAMATAN MIJEN KOTA SEMARANGTAHUN 2010-2015 - Ester Gita Kartika; Sriyono Sriyono; Hariyanto Hariyanto (Geo-Image, 2017)
The purpose of this research are: 1) Knowing the change of land area which is used by settlements in the Pesantren Urban Community 2010-2015, 2) Knowing the growth of settlement patterns and the highway corridor Semarang-Boja in the Pesantren Urban Community, 3) Knowing the factors that influencing typology of the development of settlement group on highway corridor-Boja Semarang. The analysis technique used is descriptive qualitative. The results of the research are: 1) The development of residential land in the Pesantren urban community rise about331,45% / 5 years, 2) The spread pattern of settlements in the Pesantren Urban Community using nearest neighbor analysis calculation, in order to obtain the results of T2010 = 0.21 and T2015 = 0.091 concluded that it is included on the classification of linear settlement pattern, 3) The factors of settlement development has got from a natural physical factors including the location of Pesantren Urban Community located in the northern village, Mijen and socio-cultural factorsregarding the location of residence. Pesantren Urban Community is very strategic because it is located on the highway-Boja Semarang.